Geochemistry of HCO3-Na thermal water from the Gudian slope: Insights into fluid origin, formation mechanism and circulation in the Yitong Basin, Northeast China. (April 2018) - Zhao, Rongsheng; Shan, Xuanlong; Yi, Jian; Du, Xianli; Liang, Ye; Zhang, Yunfeng
Abstract: The goal of this paper is to systematically analyze the geochemical and isotopic characteristics ( 18 O, D, T, 13 CHCO3, and DOC) of a HCO3 -Na thermal water to determine its origin, formation mechanism, and circulation pattern in the Gudian slope, Yitong Basin, Northeast China. Schoeller diagrams and isotope data indicate that this thermal water is not connected to groundwater or river water and that its recharge source is immature water with low δ 18 O and δD values that originates from the Changbaishan area. This result was also confirmed by its DOC 13 C value (approximately -24‰), which indicates that the C originates from C3 plants. The analysis of Na-K-Mg diagrams indicates that the thermal waters, except for one sample (SJXK), are fully equilibrated. This observation, combined with the results of the analysis for 18 O, D, T and cation geothermometry data for the thermal water, indicates that no water underwent mixing with cold water before arriving at the surface. Instead, high-temperature immature water flowed up from a deep reservoir and mixed with old formation water (approximately 35.4%) in the Eocene reservoir. These data indicate the occurrence of an interesting phenomenon in which the thermal water samples of the GD area exhibit a regression line with a negative slope and similar δ 18 O values, potentially due to the fractionation of CO2 gas and a buffer of high HCO3 − concentrations rather than their short circulation times. The high SO4 /Cl, B/Cl, F/Cl and HCO3 − /Cl ratios and 13 CHCO3 values (ranging from -0.84‰ to -1.24‰) of these samples imply that magmatic volatiles have been dissolved in the thermal water; however, we cannot ignore the contributions of 13 C from the leaching of limestone, with a 13 C value of approximately 3.4‰, which is further supported by the Br/Cl and HCO3 − /Cl ratios. Thus, we analyzed the geological background and data collected from well Chang-27 and deduced that a limestone stratum exists below the study area. Magmatic volatiles flow up through the lithospheric faults along the northwestern and southeastern edges of the basin, encounter Changbaishan-area recharge water in the limestone reservoir, form hot water with high concentrations of HCO3 −, and then recharged into the Eocene sandstone reservoir. Long-term mineral hydrolysis and transformation reactions in the reservoir cause the concentrations of Na to increase and lead to the formation of HCO3 -Na water. Highlights: According to 18 O, D, T and DOC data, thermal water of GD area has more than one water source in the GD area: one is CBS-area meteoric water and the other is old connate water (approximately 35.4%). The HCO3 -Na-type thermal water is not connected to groundwater or river water but is connected to deep reservoir water. Based on its geological background and δD, δ 18 O, 13 C, geothermometers data, we deduce that a limestone reservoir exists below the granite strata in the GD slope. According to ion ratios combined with 13 C values, the HCO3 -Na-type thermal waters of the GD area record not only the dissolution of magmatic volatiles but also leaching of rocks with carbonate and granite.